Morphometric Analysis of Infraorbital Foramen in Human Dry Skulls - Syeda Rizwana Jafri, Amna Muneeb, Fauzia Qureshi, Hira Sikander, Amnah Arif, Afifa Arshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and aim: The infraorbital foramen morphometric and anatomical variations is the critical factor for avoiding iatrogenic nerve injuries during surgery on the middle third of the face with safe regional anesthesia. The present study aimed to carry out the morphometric analysis of infra orbital foramen in human dry skull. Material and Methods: This morphometric study was carried out on 72 dry human skulls in the Department of Anatomy, Surayya Azeem Teaching Hospital, Lahore from January 2022 to June 2022. Research and ethical committee approved the study protocol. Skulls of identified age and gender with no apparent pathology, traumatic lesions, and deformity were enrolled. Skulls (>18 years) with bone resorption in the alveolar region and had orbital and nasal cavities damaged were excluded. Vernier caliper was used for the measurement of infra orbital foramen exact location on both sides. Transverse and sagittal diameter were measured. Infraorbital foramen and inferior margins of infraorbital margin were measured in order to determine the sagittal diameter. Infraorbital foramen medial margin to lateral margin of pyriform aperture was measured transversely. This study examined the relationship between the infraorbital foramen and the 1st premolar as well as its shape. There was also an indication of accessory foramen. SPSS version 26 was used for descriptive statistics. Results: Of the total 72 dry human skulls, there were 58 (80.6%) male and 14 (19.4%) females. The incidence of oval, triangular, semilunar, and round shape infra orbital foramen (left versus right) was (38.4% vs. 40.3%), (17.8% vs. 16.9%), (26.7% vs. 28.6%), and (17.1% vs. 14.2%) respectively. The occurrence of single and accessory intra orbital foramen was 91.8% and 8.2% respectively. The intra orbital foramen opening was directed medially downward, medially in, and downward was 34 (47.2%), 32 (44.4%), and 6 (8.3%) respectively. In association with upper teeth, the intra orbital foramen on the right and left side was 38.4% and 54.9% respectively; the buccal cusps of the maxillary second premolar teeth were located on the same vertical axis. Conclusion: The present study concluded that accurate localization of the IOF is essential to prevent infraorbital nerve injury. Additionally, foramen oval shape was the most prevalent shape followed by round shape. Knowledge regarding IOF location is critical in maxillofacial region during numerous surgery procedures which might lead to infraorbital vessels and nerve. Thus careful approach should be followed to avoid damage to foramen. Keywords: Infra orbital foramen, human skulls, morphometric analysis